Expression of Estrogen Receptor and Progesterone Receptor in Meningioma Patients - Teguh Iman Prakoso; Muhammad Thohar Arifin (HM Publisher, 2022)
Background: Meningioma is a primary intracranial benign tumor that is affected by the balance of the estrogen and progesterone hormones. This study aimed to assess the relationship between estrogen receptor (ER) expression and progesterone receptor (PR) expression in meningioma conditions. Methods: Analytical observational research with a cross-sectional study design. The number of samples is 25 meningioma patients who performed ER and PR examinations. The research was performed at Dr. Kariadi General Hospital Semarang. Statistical test using Spearman test. Results: Relationship of ER and PR to degree of meningioma is p = 0.181 (r = -0,276) and p = 0,056 (-0,387). Conclusion: There is no correlation between estrogen receptor (ER) and progesterone (PR) receptor to the degree of meningioma